Efforts to Improve Students' Learning Interest in Speaking Skills Using Interactive Method for Grade VII Students in Cibojong Garut - Ghina Zakia Mulkan; Isop Syafei; Dadan Nugraha (Gunung Djati Conference Series, 2025)
Speaking skills are essential abilities in language learning, yet many students encounter difficulties in speaking. This has prompted this research to investigate efforts to enhance students' interest in speaking skills through interactive methods in the seventh grade at Cibojong Garut. This descriptive qualitative study involved observation, interviews, and documentation to gather relevant data. The research findings indicate that interactive methods can increase students' learning interest, as evidenced by active participation, improved confidence, and enhanced learning outcomes in speaking activities. Supporting factors that contribute to this improvement include active student engagement during lessons, the use of engaging and varied media, as well as the teacher’s role in motivating students. On the other hand, several inhibiting factors were identified, such as student anxiety when speaking in front of others, limited vocabulary that restricts expression, and time constraints within the learning schedule. Therefore, implementing interactive methods consistently and creatively is crucial to foster a more positive and effective speaking learning environment.